Evaluation of agronomic traits and spectral reflectance in Pacific Northwest winter wheat under rain-fed and irrigated conditions - Gizaw, Shiferaw A.; Garland-Campbell, Kimberly; Carter, Arron H. (Field crops research, 2016)
•Variations in moisture and temperature explained 86% of total yield variation.•Grain yield was significantly correlated with spectral reflectance indices.•Subpopulations showed differentiation for agronomic and remotely sensed traits.•Earliness didn’t show net yield advantage in Pacific Northwest drought condition. The US Pacific Northwest (PNW) is characterized by high latitude and Mediterranean climate where wheat production is predominantly rain-fed and often subject to low soil moisture. As a result, selection for drought-adaptive traits in modern cultivars has been an integral component of the regional breeding programs. The goal of this research was to evaluate phenotypic associations of morpho-physiological traits and their response to soil moisture variation in winter wheat germplasm adapted to the PNW. A panel of 402 winter wheat accessions (87 hard and 315 soft) was evaluated for spectral reflectance indices (SRIs), canopy temperature (CT), plant stature, phenology, grain yield, and yield components under rain-fed and irrigated conditions in 2012–2014. Variation in soil moisture and temperature cumulatively explained 86% of total yield variation across years and locations. The phenotypic associations of yield with phenology, plant height, and CT were environment dependent. Various SRIs related to biomass, stay green, pigment composition, and hydration status showed consistent patterns of response to drought and strong correlations with yield (p<0.001). The compensatory interaction of grain number and weight was indicated in the negative correlation between thousand kernel weight and grain number per spike across moisture regimes. Area under vegetation index curve (AUVIC) explained 53–88% of the total variation in stay green estimated from visual score of flag leaf senescence (p<0.001). Principal component analysis revealed three major clusters that explained more than 76% of interrelations among traits. The market classes within the study population showed differentiation with respect to these traits. This study highlights the potential use of spectral radiometry in field screening of winter wheat for grain yield and drought adaptation in Mediterranean-like environments.